Parents’ involvement in supporting their children learn English - Isna Indriati (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2016)
This study focuses on the way of parents involving themselves in supporting their children learn English. In order to encourage children to learn better as English language learners, some parents send their children to have a continual program in non-formal institutions after schooling time. A common reason is that parents have the low capability in training their children to speak English or at least utter some meaningful words or phrases. Small scale survey by using open and closed-ended questionnaire was conducted among respondents from two elementary schools in Palangka Raya, Indonesia. They were, first, parents whose children learn English formally in SDIT Al-Furqan Palangka Raya and MIN Langkai Palangka Raya and take English course privately at home or courses center, and, second, the children as students. The questionnaires are focused on the students’ attitude and motivation towards learning English and parents’ opinions and involvement in learning the process, mainly practicing English at home. The result offers teachers some important points to consider in the teaching of English, especially the way to work with children and to build a positive relationship with parents in the regard of better learning.